ANALIZING FACTOR THAT AFFECTING IMPORT OF MAIZE IN INDONESIA ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR JAGUNG DI INDONESIA - Raditya Audayuda; Iwan Aminudin; Elpawati Elpawati (Syarif Hidayatullah State Islamic University Jakarta, 2018)
The purpose of The study is to identify the factor that affecting import of maize in Indonesia, Ana to analyze The factor that affecting import of maize in Indonesia. The data used in The Study is Time series data from 1990 to 2014 sourced from BPS(Badan Pusat Statistik) and Kementrian Pertanian. The method used in The Study is linear regression analysis using SPSS 18 software. Statistics Test that used in this Study including R2 , F-test, and T-test.In this Study we can concluded that R2 test value is 0,703 that means 70,3% import of maize explained by variable that used in model, which is: maize production (produksi jagung), maize consumption (konsumsi jagung), maize domestic prize (harga jagung domestik), maize import prize (harga jagung impor), and Rupiah to US Dollar currency (Nilai tukar rupiah terhadap dollar Amerika), and remaining 29,7% remains explained by another variable that exclude by this model. After all The testing, results shows all variable in The model affecting maize import simultaneously, and partial Test shows maize production, maize consumption, maize domestic prize, and Rupiah to US Dollar currency partially affecting import of maize in Indonesia, and maize import prize variable didn’t affect import of maize in Indonesia.